Customer Focus Among Education Service Officers in Perak - Yam, Weng Kong (1996)
This project investigated customer focus among education service officers in Ferak. The instrument was based on the Development Administration Circular 1992 of the Prime Minister’ Department in regard to the adoption of TQM in public sector. The major area for investigation was customer focus along identifying the customer and identifying requirement of the customers. A total of 458 secondary school teachers and lecturers including administrators from 21 schools and colleges in the State of Perak were surveyed through the administering of questionnaires by convenience sampling. The result showed that only about 20% of the respondents knew fully who their internal customers and external customers were. The level of customer focus in relation to service quality factors was generally high. However, regrouping of the nineteen service qualities according to the categories of customers revealed more information. Service qualities that were required by administrators scored higher than those required by students, parents and teachers. Service qualities desired by teachers was given the least attention by teachers themselves. This was the general trend discovered in this study. T-test and ANOVA were used to confirm this trend among different groups of respondents. The result of this study therefore also disproved the common belief that TQM is not necessary because what TQM advocates are already done in our schools and colleges. Recommendations were suggested to correct and to improve the effectiveness of schools and colleges through better and more relevant customer focus.